2020
DOI: 10.1101/2020.05.17.100727
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tractor: A framework allowing for improved inclusion of admixed individuals in large-scale association studies

Abstract: 38Admixed populations are routinely excluded from medical genomic studies due to concerns over 39 population structure. Here, we present a statistical framework and software package, Tractor, to facilitate the 40 inclusion of admixed individuals in association studies by leveraging local ancestry. We test Tractor with 41 simulations and empirical data focused on admixed African-European individuals. Tractor generates ancestry-42 specific effect size estimates, can boost GWAS power, and improves the resolution … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 113 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…Although we have shown that this approach improved the prediction in both African and admixed American populations, indicating that PRS-CSx is robust to imperfectly matched LD reference panels, future work is needed to better model summary statistics from recently admixed populations. One promising direction is to characterize and incorporate local ancestries in PRS construction using ancestry-specific effect size estimates 33,34 . The Bayesian modeling framework of PRS-CSx and the flexibility of continuous shrinkage priors also allow for the incorporation of functional annotations and fine-mapping results into PRS construction to improve the portability of PRS, as shown by recent studies 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Although we have shown that this approach improved the prediction in both African and admixed American populations, indicating that PRS-CSx is robust to imperfectly matched LD reference panels, future work is needed to better model summary statistics from recently admixed populations. One promising direction is to characterize and incorporate local ancestries in PRS construction using ancestry-specific effect size estimates 33,34 . The Bayesian modeling framework of PRS-CSx and the flexibility of continuous shrinkage priors also allow for the incorporation of functional annotations and fine-mapping results into PRS construction to improve the portability of PRS, as shown by recent studies 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Since the genomes of admixed individuals are a mosaic of segments with different ancestral origins, a first step would be to get ancestry‐specific effect size estimates and P ‐values from training GWASs, which is often not available from publicly available summary statistics. If individual‐level training GWAS data is available, recently developed methods like Tractor (Atkinson et al, 2020) could be applied to obtain ancestry‐specific summary statistics by generating ancestry dosage at each site from local ancestry inference calls and running a local ancestry‐aware regression. Similarly, for the validation data, local ancestry haplotype dosage for each person at each variant need to be estimated and weighted by the ancestry‐specific effect size estimated in the previous step to allow the generation of “ancestry‐specific” PRSs.…”
Section: Discussionmentioning
confidence: 99%
“…The overrepresentation of EA participants in GWAS is partly because admixed populations were long considered inconvenient in gene discovery studies, as this led to population stratification issues. However, due to advances in GWAS methods, populations with mixed genetic backgrounds can now be included in GWAS to obtain accurate estimates of SNP effects, boost power, and improve fine-mapping of effects by leveraging linkage disequilibrium differences (Asimit et al 2016;Atkinson et al 2020). Beside the general benefits to gene discovery studies, the inclusion of diverse genetic backgrounds will improve our understanding of genetic liability across diverse populations, as demonstrated for example in a study of glycemic traits (Chen et al 2021), where 30% of the participants were of non-European ancestry.…”
Section: Discussionmentioning
confidence: 99%